A view on the analytical design of future risk based residue control. Issue 5 (May 2016) - van Ginkel, Leendert A.; Sterk, Saskia S.
Abstract : The current laboratory network system in support of residue monitoring programmes within the EU formally started in the early 1990s. Since then, it has undergone a gentle evolution incorporating new techniques and methods for quality assurance and, in parallel to the extension of the European Union itself, was further extended. However, a paradigm shift from production‐based to risk‐based control now is foreseen. This will have a serious impact on the type of methodologies used and subsequently on the specific roles of EU reference laboratories also. Here, we present our view on the changes that will inevitably take place in the years to come. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : One of the tasks of EURLs is making available the analytical methods necessary for analyzing residue control samples. The shift to more risk‐based control programmes will influence this task significantly. The new food safety objectives ask for more attention for the development of protocols for the identification of new substances.